2018
DOI: 10.1016/j.str.2018.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Structure of an RNA Aptamer that Can Inhibit HIV-1 by Blocking Rev-Cognate RNA (RRE) Binding and Rev-Rev Association

Abstract: HIV-1 Rev protein mediates nuclear export of unspliced and partially spliced viral RNAs for production of viral genomes and structural proteins. Rev assembles on a 351-nt Rev response element (RRE) within viral transcripts and recruits host export machinery. Small (<40-nt) RNA aptamers that compete with the RRE for Rev binding inhibit HIV-1 viral replication. We determined the X-ray crystal structure of a potential anti-HIV-1 aptamer that binds Rev with high affinity (K = 5.9 nM). The aptamer is structurally s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 41 publications
(83 reference statements)
0
11
0
Order By: Relevance
“…The above-mentioned exceptions, where the protein–aptamer complex formation results in pronounced global conformational changes of the protein partner, include the NF-κB (p50) 2 homodimer–aptamer complex (PDB code 1OOA; ( 80 )) and the HIV-1 Rev–RNA aptamer complex (PDB code: 6CF2; ( 81 )). Compared to the NF-κB/DNA complex (PDB code 1NFK; ( 82 )), upon aptamer binding NF-κB (1OOA) undergoes an allosteric conformational change resulting in an open conformation between its N- and C-terminal domains.…”
Section: Discussionmentioning
confidence: 99%
“…The above-mentioned exceptions, where the protein–aptamer complex formation results in pronounced global conformational changes of the protein partner, include the NF-κB (p50) 2 homodimer–aptamer complex (PDB code 1OOA; ( 80 )) and the HIV-1 Rev–RNA aptamer complex (PDB code: 6CF2; ( 81 )). Compared to the NF-κB/DNA complex (PDB code 1NFK; ( 82 )), upon aptamer binding NF-κB (1OOA) undergoes an allosteric conformational change resulting in an open conformation between its N- and C-terminal domains.…”
Section: Discussionmentioning
confidence: 99%
“…This aptamer suppressed HIV production from HIV proviral clones. Finally, Dearborn et al identified small RNA aptamers that competed with the RRE for Rev binding, and predicted the structure of aptamer–Rev binding complex [ 205 ]. The structure showed that Rev’s ARM interacts with the major groove of the aptamer.…”
Section: Aptamers For Single-stranded Rna Viruses With Dna Intermediatementioning
confidence: 99%
“…Aptamers for targeting the HIV Rev protein The HIV Rev protein mediates nuclear export of unspliced and partially spliced viral RNAs. Rev assembles on a 351-nt Rev response element (RRE) within viral transcripts and induces the host's nuclear export mechanism [205]. Aptamers can act as a Rev-binding element (RBE) and therefore anti-Rev aptamers are likely a good strategy for anti-HIV therapeutics.…”
Section: Therapeutic Aptamers For Targeting Hiv Viral Proteinsmentioning
confidence: 99%
“…Another work showed that the major groove of the aptamer was bound to the arginine-rich helix domain of the target protein, Rev ( Figure 2 b), ending up with several contacts additional to those formed by the wild-type RNA. Once bound with the target protein, the aptamer would hamper Rev oligomerization at the interface [ 72 ].…”
Section: Interfaces Between Aptamer–protein Complexesmentioning
confidence: 99%